Most Probable Number of Escherichia Coli in Fresh Milk at KPSP Ijen Makmur, Licin Sub-District, Banyuwangi - Wijaya, Achmad Arby; Hamid, Iwan Sahrial; Yunita, Maya Nurwartanti; Tyasningsih, Wiwiek; Praja, Ratih Novita (Jurnal Medik Veteriner, 2021)
The study aimed to identify the total number of E. coli used in fresh cow milk in KPSP Ijen Makmur. The sample was used by as many as 16 samples from a group of cattle farmers. E. coli analyzed using Most Probable Number (MPN), 3 series of tubes. Before continuing the MPN test the milk must be diluted, 25 ml of milk was poured into the dilution of the 225ml peptone water buffered then homogenized for 2 minutes. MPN consist of presumptive coliform test if positive was found of gas and was cloudy, presumptive faecal coliform test positive was found in the gas and was cloudy, confirmed E.coli test if there was a black colony with or metallic green, continued by a biochemical test with red ring-positive Indole, Methyl Red positive the color is red, negative Voges Paskauer if there is no change in color, and negative citrate will turn green. Results showed that from the 16 samples of fresh milk used there were 7 samples of fresh milk that exceeded the contamination limit E. coli or < 3 apm /ml. Conclusion, number of E. coli in fresh milk at KPSP Ijen Makmur 43.75% of the total sample exceeded maximum contamination.